Assessing the governance of ecotourism in a forest-protected area using social network analysis: Sungei Moroli, Kampung Luanti Baru, Kawang forest reserve, Sabah - Abd Kadir, Nor Aziah; Mohd Noor, Mohd Iqbal; Azzeri, Amirah; Jaafar, Mohd Hafiz; Abdullah, Muhammad Fuad (Universiti Teknologi MARA (UiTM), 2023)
Community-based management has been heralded to practice stakeholder inclusivity and is claimed to be the panacea in overcoming problems and dilemmas in governing ecotourism in a forest-protected area. Sungei Moroli, Kawang Forest Reserve (SMKFR) at Kampung Luanti Baru Sabah, a unique destination offering Kelah fish massage is selected as the study site on account of being associated with co-management governance. This study aims to identify the key stakeholders within the governance network in this area who are involved in eco-tourism management and to understand the interests and roles of these stakeholders. Social Network Analysis (SNA) is utilized in this study. SNA is a tool to measure the criteria used, the number of ties, density, and geodesic distance, together with the degree and betweenness centralities of the network map. The social network map obtained suggests that the local community management is the most critical stakeholder in ensuring the effective operation of the ecotourism set-up in SMKFR. The bottom-up management approach with high participation and commitment of the stakeholders was indeed in place and is its critical success factor of eco-tourism activities in SMKFR. The implications of these findings to ecotourism management in the protected area for greater inclusivity of stakeholders, especially among the local communities.